2010
DOI: 10.18632/aging.100168
|View full text |Cite
|
Sign up to set email alerts
|

Chemical genetic screen identifies lithocholic acid as an anti-aging compound that extends yeast chronological life span in a TOR-independent manner, by modulating housekeeping longevity assurance processes

Abstract: In chronologically aging yeast, longevity can be extended by administering a caloric restriction (CR) diet or some small molecules. These life-extending interventions target the adaptable target of rapamycin (TOR) and cAMP/protein kinase A (cAMP/PKA) signaling pathways that are under the stringent control of calorie availability. We designed a chemical genetic screen f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
226
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 104 publications
(234 citation statements)
references
References 76 publications
(150 reference statements)
6
226
0
Order By: Relevance
“…The former is regarded as a model for dividing mammalian cells (i.e., stem cells), while the latter can be utilized as a model for non-dividing mammalian cells (i.e., neurons). 29,30 We found that, compared with the WT, replicative lifespan is significantly reduced in Δmgm1 cells (Δmgm1: 11 generations vs. WT: 23 generations) (Fig. 4A).…”
Section: Resultsmentioning
confidence: 89%
“…The former is regarded as a model for dividing mammalian cells (i.e., stem cells), while the latter can be utilized as a model for non-dividing mammalian cells (i.e., neurons). 29,30 We found that, compared with the WT, replicative lifespan is significantly reduced in Δmgm1 cells (Δmgm1: 11 generations vs. WT: 23 generations) (Fig. 4A).…”
Section: Resultsmentioning
confidence: 89%
“…This pathway stimulates transcription of the RSB1 gene; the resulting increased abundance of Rsb1p promotes further reduction of PE in the outer leaflet of the PM by (1) enhancing a stimulating effect of Rsb1p on the Lem3p-dependent transport of PE from the outer leaflet to the inner (intracellular) leaflet of the PM; and (2) amplifying an inhibitory effect of Rsb1p on the Yor1p-dependent transport of PE within the PM bilayer in the opposite direction. An ensuing depletion of PE in the outer leaflet of the PM elevates the permeability of this cellular membrane for small molecules (such as propidium iodide 1,71 ), thereby contributing to the commitment of yeast to liponecrotic PCD.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6]16,20,25,31,33,56 Of note, we found that a treatment of yeast cells with LCA alters the agerelated chronology of these mitochondrial processes. 5,36,38,[68][69][70] We therefore hypothesized that LCA may impact not only the levels of numerous mitochondrial proteins but also the levels of proteins in cellular locations outside mitochondria. To validate our hypothesis, we used quantitative mass spectrometry to compare proteins that were recovered in total lysates of WT cells cultured in the presence of LCA or in its absence.…”
Section: Lca Elicits Age-related Changes In Mitochondrial Proteomementioning
confidence: 99%
“…These cellular processes include the following: (1) glycogen degradation; (2) the glycolytic pathway; (3) the pentose phosphate pathway; (4) pyruvate conversion to acetyl-CoA; (5) the maintenance of redox balance between NAD and NADH with the help of carnitine and glycerol-3-phosphate shuttles; (6) ROS detoxification; (7) stress response; (8) glutathione synthesis; (9) gluconeogenesis; (10) ethanol formation; (11) the synthesis and hydrolytic degradation of triacylglycerols (TAG) and ergosteryl esters (EE), the 2 major neutral lipids; (12) the synthesis of various amino acids; (13) nucleotide synthesis; (14) the assembly of the 40S and 60S ribosomal subunits from numerous protein components whose levels were altered by LCA; and (15) proteasomal and vacuolar protein degradation. 4,5,39,41,38,71,72 We then subjected cellular proteins whose levels were changed in yeast grown in a medium supplemented with LCA to bioinformatic analysis with the help of the SPELL online search engine, 51 as described above for mitochondrial proteins. Just as our bioinformatic analysis of mitochondrial proteins revealed (see above), we found that each of the cellular proteins whose level was altered in yeast cultured with LCA belongs to the following 2 multi-clustered regulons: (1) the PMD regulon, which consisted of the rho 0 (Rtg2p governed) cluster, S1 cluster, general TCA cycle dysfunction cluster, kgd1D, kgd2D or lpd1D cluster, yme1Dmdl1D Figure 2.…”
Section: Lca Elicits Age-related Changes In Mitochondrial Proteomementioning
confidence: 99%
See 1 more Smart Citation